The Neurobiological Underpinnings of Psychoanalytic Theory and Therapy - Solms, Mark Leonard (Frontiers in Behavioral Neuroscience, 2018)
This paper sets out the neurobiological underpinnings of the core theoretical claims of psychoanalysis. These claims concern (1) innate emotional needs, (2) learning from experience, and (3) unconscious mental processing. The paper also considers the neurobiological underpinnings of the mechanisms of psychoanalytic treatment—a treatment which is based on the aforementioned claims. Lastly, it reviews the available empirical evidence concerning the therapeutic efficacy of this form of treatment.